The Effect of Profitability, Tax Planning, Independent Commissioners, and Firm Size on Firm Value: Evidence from the Indonesian Financial Sector - Zoey Felicia; Juan Carlos Pangestu (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The value of a firm is a critical concern for stakeholders, especially in the financial sector, where internal governance and financial strategies play a vital role. This study investigates the influence of profitability, tax planning, independent commissioners, and firm size on firm value in financial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The research problem centers on identifying which internal factors significantly contribute to enhancing firm value in the post-pandemic recovery phase. The study aims to analyze these relationships using a quantitative approach. Secondary data were collected from audited annual financial statements and official company websites. A total of 152 financial companies were selected through purposive sampling. Data analysis was performed using SPSS version 25.0, applying descriptive statistics, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). The findings reveal that profitability and the presence of independent commissioners have a positive and significant effect on firm value. Conversely, tax planning and firm size do not show a significant influence. These results offer practical implications for company management, investors, and policymakers in identifying and reinforcing internal factors that drive firm value in Indonesia's financial sector. The study adds to the limited literature focusing on this sector, especially during the multi-year recovery period following the COVID-19 pandemic.